Key Performance Factors in Implementing Public Construction Projects Using Force Account Method [FAM]: A Systematic Literature Review (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
This study reviewed performance factors influencing the implementation of public building construction projects using the force account method. The Force Account Method [FAM] has been effectively used in public construction projects since 2016, offering advantages such as lowering costs and creating job opportunities. Nevertheless, there are still obstacles to overcome, such as ineffective time management, cost control issues, quality control, improper procurement processes, and inadequate supervision. Through a systematic literature review, this study identified key performance factors across different phases of the construction project, which are planning, design, procurement, and construction. The most significant factors are effective project planning, adequate project design, procurement management, and effective construction supervision. Additional critical factors include the competence and adequacy of project participants, as well as effective leadership and government support. These factors are interrelated and essential for ensuring the effective implementation of public construction projects using the force account method. The study ends by suggesting that a framework be created to better manage the execution of construction projects using the force account method, making sure that each phase follows best practices in construction management and fixes any problems that were found.